Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd008933
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulators and immunosuppressants for multiple sclerosis: a network meta-analysis

Abstract: Background Different therapeutic strategies are available for treatment of multiple sclerosis (MS) including immunosuppressants, immunomodulators, and monoclonal antibodies. Their relative effectiveness in the prevention of relapse or disability progression is unclear due to the limited number of direct comparison trials. A summary of the results, including both direct and indirect comparisons of treatment effects, may help to clarify the above uncertainty. Objectives To estimate the relative efficacy and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…29 This suggests that any differences in relapse activity between the injectable immunomodulators are minimal and detectable only on sufficient follow-up duration. In their network meta-analysis, Filippini and colleagues used a combination of direct and indirect comparisons to estimate relative treatment efficacy among the commonly used disease-modifying therapies, including IFNβ and GA. 30 In agreement with our findings, the meta-analysis showed superiority of IFNβ-1a SC over the other IFNβ preparations in their effect on relapse outcomes. In addition, unlike our analysis, it reported superiority of IFNβ-1a SC over GA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…29 This suggests that any differences in relapse activity between the injectable immunomodulators are minimal and detectable only on sufficient follow-up duration. In their network meta-analysis, Filippini and colleagues used a combination of direct and indirect comparisons to estimate relative treatment efficacy among the commonly used disease-modifying therapies, including IFNβ and GA. 30 In agreement with our findings, the meta-analysis showed superiority of IFNβ-1a SC over the other IFNβ preparations in their effect on relapse outcomes. In addition, unlike our analysis, it reported superiority of IFNβ-1a SC over GA.…”
Section: Discussionsupporting
confidence: 92%
“…30 Therefore, the outcomes of network meta-analyses may be susceptible to confounding introduced by the heterogeneity of indirectly compared trial populations. Our analysis used matched head-to-head comparisons with uniform inclusion criteria and follow-up protocol, and was therefore relatively resistant to population heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…These compare favourably, to within a 10% range, which is adequate for approximate comparisons. More formal attempts to compare trials using network meta-analysis and similar approaches have shown conflicting results [65][66][67][68]. What is striking in the comparison shown in Table 1 is the high degree of concordance between the observed effect on Gad-enhancing lesions and relapse rates and between measures of brain atrophy and disability progression in what is a very consistent pattern across therapies.…”
Section: Comparative Efficacymentioning
confidence: 99%
“…It was largely abandoned as a first-line therapy in many countries in the mid-1990s when the b-interferons ushered in a new generation of MS therapeutics [165]. However, recently, new findings showed the possibility to consider azathioprine as an inexpensive treatment option for RRMS.…”
Section: Azathioprinementioning
confidence: 99%